Understanding the Role of Business Analytics Some Applications - Chahal, Hardeep; Jyoti, Jeevan; Wirtz, Jochen (Springer Nature Singapore : Imprint: Springer, 2019)
XV, 205 p. 51 illus., 48 illus. in color.